1999
DOI: 10.2115/fiber.55.11_542
|View full text |Cite
|
Sign up to set email alerts
|

Structural Change of High-Speed Spun Poly (ethylene 2,6-naphthalene dicarboxylate) Fibers with Annealing.

Abstract: The as-spun poly(ethylene 2,6-naphthalene dicarboxylate)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…This also predicts that the necking position shift toward the spinneret with increasing take-up speed, as observed by Iizuka and Yabuki 88 and Miyata et al 32 In addition to the b modification, the a modification could also form in the PEN fibers by the aid of the spinline stress. 32,68,73,82,90 It was reported that the content of the a crystals increased with increasing take-up speed. 68 At the same time, the amount of the a crystals relative to that of the b crystals decreased 32 because the content of the b crystals increased more rapidly at higher speeds.…”
Section: Stress-induced Crystallizationmentioning
confidence: 99%
See 3 more Smart Citations
“…This also predicts that the necking position shift toward the spinneret with increasing take-up speed, as observed by Iizuka and Yabuki 88 and Miyata et al 32 In addition to the b modification, the a modification could also form in the PEN fibers by the aid of the spinline stress. 32,68,73,82,90 It was reported that the content of the a crystals increased with increasing take-up speed. 68 At the same time, the amount of the a crystals relative to that of the b crystals decreased 32 because the content of the b crystals increased more rapidly at higher speeds.…”
Section: Stress-induced Crystallizationmentioning
confidence: 99%
“…The semicrystalline PEN fibers often contain oriented amorphous portion which can further crystallize during heat-treatment. Miyata et al 82 found that when constrained annealing the PEN as-spun fibers, which had been either crystallized into the b modification at higher take-up speeds, or remained amorphous at lower take-up speeds, at temperatures from 200 to 2808C, the a modification always formed. Once the annealing temperature was raised to 2808C, the b modification started to appear in the fibers even if the fibers had been taken up at low speeds.…”
Section: Stress-induced Crystallizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, however, the result reported by Buchner et al, which was cited in the report by Miyata et al [29] on high-speed spun PEN fibers produced from 'same' pellets, was used for indexing the reflections assigned to b-modification in our SAED patterns, because in our next paper the uniaxially oriented thin film of PEN will be morphologically compared with the high-speed spun PEN fibers.…”
Section: Resultsmentioning
confidence: 99%